Design, synthesis and biological evaluation of carbazole derivatives as antitubercular and antibacterial agents - Sellamuthu S.; Bhat M.F.; Kumar A.; Nath G.; Singh S.K. (My University, 2025)
Background: The neuroleptic chlorpromazine has been reported for antitubercular activity but the associated antipsychotic activity restricted its clinical presentation. Objectives: Novel derivatives of carbazole having structural similarity with chlorpromazine were designed, in an attempt to reduce the associated side effects, while retaining the antitubercular activity. Materials and Methods: The designed molecules were synthesized and screened for antitubercular and antibacterial activities. The blood-brain barrier (BBB) permeability and mammalian cell (VERO) cytotoxicity (CC50) were examined to determine the safety of compounds. Results: Among the developed compounds, 14c, 15c, 16c and 17c were found to be promising against Mtb H37Rv at MIC of 1.56 μg/ml. They were also effective against S. aureus and E. coli at MIC of 0.98 and 7.81 μg/ml, respectively. The BBB permeability of the compounds was found to be less than chlorpromazine. Therefore, the developed compounds are expected to have diminished antipsychotic effect. The compounds were further marked safe against mammalian VERO cells at CC 50 > 90 μg/ml. Conclusion: The profound antitubercular activity with a concomitant reduction in BBB permeability of carbazole derivatives can pave new vista in the discovery of antitubercular drugs. © 2019 Bentham Science Publishers.